(untitled) (Comprehensive Journal of Science, 2026)
This study examines the relationship between psychological optimism and social adaptation in crisis conditions through a systematic review of peer-reviewed studies published between 2018 and 2025. The scientific literature reveals that optimism is not merely a transient personality trait but a strategic psychological resource that significantly enhances individual and collective resilience when crises strike—whether pandemics, armed conflicts, or natural disasters. Employing a descriptive-analytical methodology grounded in critical review of primary sources, the study analyzed over thirty Arabic and international peer-reviewed studies. Findings consistently indicate a statistically significant positive relationship between optimism levels and social adaptation, mediated by psychological resilience, social support, and effective coping strategies. Evidence further shows that optimism attenuates post-traumatic stress and crisis-related depression while strengthening family and social cohesion. The review concludes by emphasizing the need to integrate optimism-building programs into health and educational systems, particularly in Arab contexts—including Libya—that remain underrepresented in the empirical literature despite facing compounding stressors from years of instability.